2017
DOI: 10.1242/jcs.212308
|View full text |Cite
|
Sign up to set email alerts
|

Giantin-knockout models reveal a feedback loop between Golgi function and glycosyltransferase expression

Abstract: The Golgi is the cellular hub for complex glycosylation, controlling accurate processing of complex proteoglycans, receptors, ligands and glycolipids. Its structure and organisation are dependent on golgins, which tether cisternal membranes and incoming transport vesicles. Here, we show that knockout of the largest golgin, giantin, leads to substantial changes in gene expression but only limited effects on Golgi structure. Notably, 22 Golgi-resident glycosyltransferases, but not glycan-processing enzymes or th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 46 publications
5
65
0
Order By: Relevance
“…Our results clearly indicate that Golgi biogenesis requires giantin, and this finding harmonizes well with recently published data by Stevenson et al that the recovery of Golgi after BFA was abolished in the giantin KO model [54]. While we observed the reduction of cisternal length in cells lacking giantin, these authors could not detect significant changes in this Golgi parameter.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results clearly indicate that Golgi biogenesis requires giantin, and this finding harmonizes well with recently published data by Stevenson et al that the recovery of Golgi after BFA was abolished in the giantin KO model [54]. While we observed the reduction of cisternal length in cells lacking giantin, these authors could not detect significant changes in this Golgi parameter.…”
Section: Discussionsupporting
confidence: 93%
“…Our results thus far suggest that giantin is essential for the biogenesis of Golgi in terms of its compact structure and perinuclear localization. However, in giantin-depleted cells, GM130-and GRASP65-specific immunostainings do not seem significantly different from the cells transfected with control siRNAs, at least at the level of conventional multi-fluorescence microscopy [13,54,105]. This suggests that cells that are not under the treatment with Golgi disturbing agents but are experiencing a deficiency in giantin may launch a Thus, cells lacking detectable giantin appear to possess Golgi stacks and perinuclear location due to GRASP65 oligomerization.…”
Section: Is Grasp65 the Protein That May Compensate For The Lack Of Gmentioning
confidence: 94%
“…Giantin-depleted cells produce fewer cilia and those that remain are longer, suggesting a defect in length control. In contrast, analysis of giantin KO RPE-1 cells (Stevenson et al, 2017) shows no gross defects in ciliogenesis at the level of light microscopy ( Fig. 1A, quantified in B) or any significant change in cilia length (Fig.…”
Section: Results and Discussion Giantin Ko Cells Show No Gross Defectmentioning
confidence: 89%
“…We recently generated a KO cell line that no longer expresses giantin (Stevenson et al, 2017). Here, we show that in contrast to depletion of giantin, complete knockout of the gene does not prevent cells from generating cilia on serum withdrawal.…”
Section: Introductionmentioning
confidence: 81%
“…On the contrary, other studies have observed that disorganization of ribbon architecture is not lethal and does not cause extensive changes in glycosylation [132][133][134]. To explain the mechanistic basis of its contribution to glycosylation, several hypotheses have been proposed: facilitation of homogenous distribution of GTs across stacks [135], regulation of the kinetics of intra-Golgi transport so as to provide optimal time for cargo processing [136] and finally regulation of glycogene transcript levels [137]. However, others have observed no change in glycosylation [138] or a general alteration in transport kinetics [139] following disruption of Golgi ribbon architecture.…”
Section: Golgi Organizationmentioning
confidence: 99%